2009
DOI: 10.1111/j.1365-2249.2009.03926.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of muramyl dipeptide stimulation of cytokine production by blood components

Abstract: SummaryMuramyl dipeptide (MDP) is the minimal active fragment of peptidoglycan of the cell wall of Gram-positive bacteria, with potential beneficial effects as a vaccine adjuvant. Peptidoglycans and MDP are recognized by the intracellular receptor NOD2 (nucleotide-binding oligomerization domain 2), leading to production of proinflammatory cytokines. In the present study, it is shown that, despite stimulatory effects on isolated human mononuclear cells, MDP does not stimulate production of tumour necrosis facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 24 publications
(28 reference statements)
1
12
1
Order By: Relevance
“…This would mean that the highest dilution of pustulan in the WBA (25μg/ml) - which still gave strong cytokine responses - contained maximally 45 ng/ml PGN. Rockel et al 33 reported that PGN alone does not stimulate a cytokine response in human whole blood at 10 μg/ml, and van der Meer et al 34 found the same result for muramyldipeptide in human whole blood. Thus the concentration of PGN measured in our glucan preparations was clearly below the minimum level required for cytokine induction.…”
Section: Discussionmentioning
confidence: 88%
“…This would mean that the highest dilution of pustulan in the WBA (25μg/ml) - which still gave strong cytokine responses - contained maximally 45 ng/ml PGN. Rockel et al 33 reported that PGN alone does not stimulate a cytokine response in human whole blood at 10 μg/ml, and van der Meer et al 34 found the same result for muramyldipeptide in human whole blood. Thus the concentration of PGN measured in our glucan preparations was clearly below the minimum level required for cytokine induction.…”
Section: Discussionmentioning
confidence: 88%
“…Similarly to Candida stimulation, LPSinduced IL-1b and TNF-a production by PBMCs was lowered in the presence of PMNs (Fig. 1B) (21). To investigate whether the decreased cytokine concentration could be explained by internalization of the cytokine in the cell or by binding of the cytokine to membrane-bound receptors, we measured the concentration of TNF in the cells lysed in Triton-X, which represents the concentration of intracellular and membrane-bound TNF.…”
Section: Resultsmentioning
confidence: 93%
“…Recently, we made the observation that neutrophils modulate cytokine production stimulated by bacterial peptidoglycans and LPS (21). As both neutrophils and proinflammatory cytokines are essential in host defense against C. albicans, we investigated whether neutrophils could also modulate cytokines produced by PBMCs after stimulation with Candida.…”
mentioning
confidence: 99%
“…For instance, neutrophils release proteases that not only degrade extracellular matrices and cells surrounding the inflammatory milieu but also deactivate inflammatory cytokines ( 180 ). Additionally, neutrophils modulate the cytokine production stimulated by bacterial peptidoglycans and LPS ( 181 ). In vitro studies have shown that PMN lysates and neutrophil elastase can degrade recombinant human IL-1β and TNF-α but not IL-10, and alpha1-antitrypsin can inhibit this process ( 180 ).…”
Section: How Does Resolution Start?mentioning
confidence: 99%